Comparison of enamel hardness after dental bleaching agent application strawberry gel and carbamide peroxide 10% - Asmawati Asmawati; Irene E. Rieuwpassa (Journal of Dentomaxillofacial Science, 2018)
Objective: Carbamide peroxide 10% is commonly used in home bleaching procedure. Effectiveness of carbamide peroxide bleaching process as a home bleaching has no successor yet, but its use is still being debated due to the effects on oral cavity. Strawberries are one of natural ingredients that currently used to whiten decolorized teeth because it contains ellagic acid and malic acid. On contrary, malic acid is said to be involved in the process of erosion. The aim of this study was to compare tooth enamel hardness after application of dental bleaching agent carbamide peroxide 10% and strawberry gel.Material and Methods: Sample consists of 30 maxillary incisors were divided into 3 groups. The first group as control soaked in aquades. The second treatment group were applied with carbamide peroxide 10%Â  and a third group applied with strawberry gel. Before and after the sample application, tests were performed to determine the hardness of tooth enamel as measured using Universal Hardness Tester.Results: Based on Friedman test, p-value = 0,000 (p <0,05; significant). This means that there was a significant difference in tooth enamel surface hardness of each group and treatment group using bleaching carbamide peroxide 10% and strawberry gel.Conclusion: There was a decrease on tooth enamel hardness after application of carbamide peroxide 10%Â  compared strawberry gel.